Synergistic doping effects of a ZnO:N/BiVO4:Mo bunched nanorod array photoanode for enhancing charge transfer and carrier density in photoelectrochemical systems. Issue 43 (26th October 2018) - Kim, Donghyung; Zhang, Zhuo; Yong, Kijung
Abstract : One-dimensional heterojunction nanorods are highly attractive as photoanodes for developing efficient photoelectrochemical (PEC) systems for the effective photogeneration of charge carriers and transport. Abstract : One-dimensional heterojunction nanorods are highly attractive as photoanodes for developing efficient photoelectrochemical (PEC) systems for the effective photogeneration of charge carriers and transport. ZnO/BiVO4 nanorod arrays (NRAs) are excellent candidates if their charge transferring and recombination issues can be improved. In the current work, we have studied the synergistic doping effects of N-doped ZnO/Mo-doped BiVO4 NRAs for enhancing the photoanode activity in PEC devices. The N-doping of ZnO NRs enhances the charge carrier density ∼3-fold over undoped ZnO NRs through increased oxygen vacancies induced by N dopants. The Mo dopants in BiVO4 improve the mobility of photogenerated charge carriers and contribute to reducing charge recombination. The synergistic doping effects of both ZnO and BiVO4 could increase the charge transfer rate constant ( k ct ) of the ZnO:N/BiVO4 :Mo heterojunction by ∼40% and decrease the charge transfer resistance ∼1.9-fold compared to those of undoped ZnO/BiVO4, which were confirmed by time resolved photoluminescence (PL) and electrochemical impedance (EIS) analyses. Our optimally fabricated ZnO:N/BiVO4 :Mo NRA photoanode could achieve an excellent photocurrent of 3.62 mA cm −2 without the application of any co-catalysts. This work presents a useful strategy for designing efficient heterojunction photoanodes in PEC systems.